Multiple insertions of COIN, a novel maize Foldback transposable element, in the Conring gene cause a spontaneous progressive cell death phenotype. (26th August 2020) - Kim, Saet‐Byul; Karre, Shailesh; Wu, Qingyu; Park, Minkyu; Meyers, Emily; Claeys, Hannes; Wisser, Randall; Jackson, David; Balint‐Kurti, Peter
SUMMARY: Similar progressive leaf lesion phenotypes, named conring for "concentric ring, " were identified in 10 independently derived maize lines. Complementation and mapping experiments indicated that the phenotype had the same genetic basis in each line – a single recessive gene located in a 1.1‐Mb region on chromosome 2. Among the 15 predicted genes in this interval, Zm00001d003866 (subsequently renamed Conring or Cnr ) had insertions of four related 138 bp transposable element (TE) sequences at precisely the same site in exon 4 in nine of the 10 cnr alleles. The 10th cnr allele had a distinct insertion of 226 bp of in exon 3. Genetic evidence suggested that the 10 cnr alleles were independently derived, and arose during the derivation of each line. The four TEs, named COIN a (for COnring INsertion) through COIN d, have not been previously characterized and consist entirely of imperfect 69‐bp terminal inverted repeats characteristic of the Foldback class of TEs. They belong to three clades of a family of maize TEs comprising hundreds of sequences in the genome of the B73 maize line. COIN elements preferentially insert at TNA sequences with a preference for C and G nucleotides in the immediately flanking 5′ and 3′ regions, respectively. They produce a three‐base target site duplication and do not have homology to other characterized TEs. We propose that Cnr is an unstable gene that is mutated insertionally at high frequency, most commonly due to COIN element insertions at a specific site in the gene. Significance Statement: By investigating the basis of an unusual mutant phenotype, we have identified two interesting genetic features, i.e., the Conring gene that appears to act as a suppressor of the lateral spread of cell death and a novel family of Foldback transposable elements that we have called COIN elements.